Adults in Ghana generate higher and more durable neutralising antibody titres following primary course COVID-19 vaccination than matched UK adults: The HERITAGE Study - Eliza Mari Kwesi-Maliepaard; Yakubu Alhassan; Emmanuel K. Quaye; Vera M. Kotey; Aisha M. Mohammed; Seth Agyemang; Adelaide K. Sromani; Stephanie Darko; Erica Buadii; Randy Tackie; Harry Akligoh; Barikisu Ibrahim; et al. (BMC Medicine)
Abstract Background Little data exist on the COVID-19 vaccine response in African countries who despite having high disease burden, have low COVID-19 mortality rates. We investigated the longitudinal immune response in a West-African urban population upon COVID-19 vaccination, two years after the start of the pandemic. Methods The HERITAGE study is a prospective cohort study of 301 residents of Accra, Ghana. Participants received two doses of a COVID-19 vaccine (AZD1222 or BNT162b2) from December 2021 and were followed-up for 12 months. COVID-19 status was determined by RT-PCR at seven time points. Serological responses, including anti-Nucleocapsid IgG, anti-Spike IgG and live-virus neutralisation were determined at four time points during the 12 months follow-up. Results COVID-19 positivity was 19.3% at baseline and reduced rapidly upon vaccination. Serological analyses indicated previous exposure to SARS-CoV-2 in 80.5% of the HERITAGE participants. After vaccination, neutralising antibody titres (NAbTs) against six different SARS-CoV-2 variants significantly (p < 0.001) increased, with fold changes (FC) ranging from 1.87 to 4.59. Highest NAbTs were recorded in the previously exposed group. Participants without prior exposure showed a continues increase in NAbTs between months 3 and 12 for circulating variants (Omicron B.A2 (FC 2.44, p < 0.001) and XBB.1.5 (FC 1.91, p = 0.05)). By comparison a matched cohort from the UK-based LEGACY study showed generally lower NAbTs at baseline (HERITAGE vs LEGACY for Wild-type: 250.3 vs 141.3, p < 0.0001, for A.27 84.6 vs 43.2, p = 0.0129, for Eta 159.7 vs 118.1, p = 0.3428, for Delta 158.6 vs 10.0, p < 0.0001, for Omicron B.A2 153.7 vs 10.0, p < 0.0001) and after receiving the vaccine (HERITAGE vs LEGACY for Wild-type: 882.6 vs 337.7, p < 0.0001, for A.27 552.0 vs 227.7, p = 0.0001, for Eta 682.2 vs 295.3, p < 0.0001, for Delta 557.6 vs 165.1, p < 0.0001, for Omicron B.A2 283.3 vs 124.2, p < 0.0001). NAbTs kinetics between the two cohorts were more similar when analysis was restricted to previously unexposed participants when adjusted for circulating variants during the sampling period. Conclusions Two doses of AZD1222 or BNT162b2 significantly increased existing NAbTs against SARS-CoV-2 in a highly exposed population, showing durable boosting of pre-existing infection-induced immunity. This indicates the importance of considering local population exposure in vaccination design and deployment.